IMPACT OF LEAD ACETATE ON GROWTH PARAMETERS AND BEHAVIOUR IN BUNNI MESOPOTAMICHTHYS SHARPEYI - Al-Rudainy, Abdulmotalib; Mustafa , Sana; Salman, Noor (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A total of 100 fingerlings of Bunni, Mesopotamichthys sharpeyi weighing between 10-15g were used in the current experiment. The experimental fish treatments involved adding different concentrations of lead acetate exposure as follows: T1 control treatment ; T2 and T4 exposed to 0.2mg/l and 0.4mg/1 of lead acetate with complete replacement of water aquarium every two days and added lead acetate continuously in the same proportion. T3 and T5 exposed to lead acetate of 0.2 and 0.4 mg/l in first time only without adding the above percentage of lead acetate with complete replacement of water aquarium every two days. , Results showed after 30 days of exposure that the total weight gain ranged between -5.14g to 3.69g in T2 and T1 respectively.Values of Relative growth rate (RGR) ranged from -38.64-30.59% in T2 and T1 respectively, while the values of specific growth rate (SGR) ranged between -0.0018-0.0039 % / day respectively in the same treatments. The study found that higher concentrations of lead (0.4 mg/l) and continuous exposure had the most detrimental effects on the weight loss, feed intake and the behavior of fish.